HUSBAND'S SUPPORT FOR REGULARITY OF ANTENATAL CARE (ANC) (IN THE VILLAGE POLYCLINIC IN DRENGES VILLAGE, SUGIHWARAS DISTRICT BOJONEGORO REGENCY) - Fajrin, Fitriana Ikhtiarinawati (Universitas Nahdlatul Ulama Sidoarjo, 2019)
This study aims to determine the support of the husband, know the regularity of antenatal care and analyse the relationship of husband's support for the regularity of antenatal care. This research is a descriptive analytic study with Cross Sectional approach. Sources of data were obtained from all pregnant women who examined at the village polyclinic in Drenges Village, Bojonegoro Regency on November 1, 2017 - May 1, 2018 with a population of 28 people. The sampling technique uses Total Sampling. Data collection techniques use primary data and secondary data. Primary data in the form of data about husband's support for antenatal care obtained from the questionnaire, while secondary data in the form of data about the regularity of antenatal care obtained from medical records and MCH books, then the data were analyzed descriptively and by statistical analysis using SPSS 22 correlation test. The results of this study indicate that the majority of husbands' support is lacking as many as 19 respondents (68%), the majority of respondents do not regularly conduct Antenatal Care examinations as many as 17 respondents (61%), the majority of respondents who received husband’s support regularly conducted Antenatal Care, namely 6 respondents (67 %), and respondents who lacked husband's support, the majority of them did not regularly conduct Antenatal Care, namely 14 respondents (74%). From the results of the correlation test, the value of sig = 0,000 means that H0 is rejected and H1 is accepted. From the results of the correlation test also obtained a correlation coefficient of 0.8 which means that the support of the husband with the ANC regularity is very strong. The conclusions from this study are the relationship between husband's support and the regularity of the ANC with a very strong relationship.